Derrida’s Criticism of Husserl Reconsidered: Historicity, Ideality and the Phenomenon of Voice - Hopkins, Burt C. (Bollettino Filosofico, 2021)
The importance of Derrida’s pre-deconstructive critique of Husserl’s last phenomenological works for his deconstructive critique of his first work will be demonstrated. On the basis of this, I argue 1) the importance of Derrida’s embrace of Husserl’s account of the coincidence of historical and ideal meaning in the Crisis of European Science and Transcendental Phenomenology for his deconstructive critique of signification in the Logical Investigations as paradigmatic for Husserl’s phenomenology as a whole; 2) Derrida’s historically driven appeal to role of the phenomenon of the voice in the epoch of metaphysics cannot withstand historically critical scrutiny; and 3) one result of 2) is to render Derrida’s deconstruction of Husserl null and void. Keywords: Deconstruction, Derrida, Historicity, Husserl, Ideality